Exploring the Online Learning Experience of Filipino College Students During Covid-19 Pandemic - Giray, Louie; Gumalin, Daxjhed; Jacob, Jomarie; Villacorta, Karl (SCAD Independent, 2022)
This study was endeavored to understand the online learning experience of Filipino college students enrolled in the academic year 2020-2021 during the COVID-19 pandemic. The data were obtained through an open-ended qualitative survey. The responses were analyzed and interpreted using thematic analysis. A total of 71 Filipino college students from state and local universities in the Philippines participated in this study. Four themes were classified from the collected data: (1) negative views toward online schooling, (2) positive views toward online schooling, (3) difficulties encountered in online schooling, and (4) motivation to continue studying. The results showed that although many Filipino college students find online learning amid the COVID-19 pandemic to be a positive experience such as it provides various conveniences, eliminates the necessity of public transportation amid the COVID-19 pandemic, among others, a more significant number of respondents believe otherwise. The majority of the respondents shared a general difficulty adjusting toward the new online learning setup because of problems related to technology and Internet connectivity, mental health, finances, and time and space management. A large portion of students also got their motivation to continue studying despite the pandemic from fear of being left behind, parental persuasion, and aspiration to help the family.